Peningkatan Sumber Daya Manusia (SDM) Desa melalui Sosialisasi Pentingnya Perencanaan Keuangan demi Kebebasan Finansial Masyarakat Desa Binaus, Kabupaten Timor Tengah Selatan (TTS) - Ardiman, Yohanes; Ismawati, Hilda Karman; Mur, Elsiana; Bani, Angelina; Nirta, Rosalia; Bau, Maria Novita; Bhebhe, Maria Casandra; Hale, Maria Indrayani; Diron, Ludovikus Kelvino; Wea, William Gilbert; Talu, Maximus; Migo, Maria Stefania D.; Olin, Maria Virginia Stefani; Pereira, Intan Patricia A.; Sukmawati, Sukmawati; Klau, Stefania Seuk; Burin, Stefanie Noviega B.; Goetha, Selfiana; Manafe, David (Universitas Pahlawan Tuanku Tambusai, 2026)
Financial planning is an essential skill that enhances human resource (HR) quality and supports rural communities in achieving economic independence. The people of Binaus Village, South Central Timor Regency, face challenges in financial management due to fluctuating incomes, consumptive spending habits, and low saving awareness. This community engagement program aims to improve financial literacy through socialization and training using the Participatory Action Research (PAR) method, which involved observation, interviews, focus group discussions, and practical workshops on financial recording, budgeting, and saving strategies. The results indicate a positive shift in community mindset, from short-term consumption toward more productive financial allocations, including education, health, and emergency savings. The study concludes that contextual financial planning socialization can strengthen financial awareness, reduce dependence on high-interest loans, and guide rural communities toward sustainable financial freedom.